Pengaruh Ketidakpastian Lingkungan dan Desentralisasi terhadap Karakteristik Sistem Akuntansi Manajemen - Aida Ainul Mardiyah; Gudono Gudono (The Indonesian Journal of Accounting Research, 2013)
This study intends to identify the interactive effect of environmental uncertainty and decentralization on management accounting systems design. Management accounting systems design was defined in term of perceived availability of characteristics of information, namely, broad scope, timeliness, aggregation, and level of integration (Chenhall dan Morris, 1986). Data is selected using random sampling. The analysis units for responses of 66 ma-nagers ¾ production and marketing¾. The data collection is performed using mail survey. The statistic method used to test the hypotheses is multiple regression ¾ multiplicative model and nonmonotonic effect¾ and MANOVA. In addition, an analytical method of utilizing partial derivative to test the contingency relationship as advocated by Waterhouse dan Tiessen (1978); Schoonhoven (1978); Govindarajan (1986); Chia (1995); Fisher (1996); and Nazaruddin (1998) was also used.The study results are as follows: first, The results provide support for the hypothesis that environmental uncertainty and decentralization have an interactive effect on  information characteristics of management accounting systems. More specifically, the results showed that decentralization significantly moderates the relationship between environmental uncertainty and information characteristic management accounting systems. The greater the degree of decentralization, the stronger the effect of high environmental uncertainty on degrees  of sophisticated information characteristics; second, the normal data test and non response bias using t-test shows an insignificant result. This means that there are non response bias and the normal data; third, this is demonstrated by the multicolinearity number r< 0,8 or VIF mean 1  that shows that the multicolinearity is not dangerous, the Durbin Watson  approaches 2 and BG (The Breussh-Godfrey) r=0  which means that between one variable and the other there is no dependency relationship (independent), and and homoscedacity occur.